Processos comunicacionais no contexto de oficinas livres de dança: caminhos para expressão criativa do corpo - Rios, Carlos Eduardo Borrely (2013)
What are the characteristics of the communication process that happen during dance workshops between teacher and students? How can those procedures generate process in such a way that everyone involved is able to be part of unique ways of expression? How can we stimulate body experiences through American tap dance techniques? Those are the questions that build this research. The principal objective was to think about how the creative and communication processes work together during the mediation of an expressive movement discovery. The mediations and creative and cognitive processes are based in communication theories. Some of the authors used are Flusser, Santaella and Viera. The bodymedia background by Katz and Greiner, and the mental imaged studies by Damásio improve the reference bases. The proposal is to think and converse with other procedures by Klaus Vianna who developed a body expression based method. The methodology includes bibliographical research; collect and organization of documents about the creation during the workshops (diaries, drawings and videos); procedures analysis through the process theory view and reflexive memorial about teaching activities. We hope this research, while we document workshops's creative process and organize those reflections about communication relations lived during this context, can contribute with the bodymedia studies